(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2022)
Chronic Lymphocytic Leukemia (CLL) has shown great biological heterogeneity, with a variable prognosis, and a short survival in some patients. In this light, the present study focused on the prognostic utility of circulating microparticles (MPs) and a Thrombin Generation (TG) Profile for thrombotic risk and disease progression in CLL patients. Circulating microparticles and TG were evaluated in 35 patients with CLL and 35 healthy individuals. For circulating microparticles, significant differences were observed among the following groups: MPs derived from endothelial cells (p = 0.002), B lymphocytes (p < 0.001), platelets (p = 0.003), and Tissue Factor MPs in monocytes (p < 0.001). In all cases, MP values were higher for the CLL group. When compared to the controls, CLL patients presented a decrease in TG, characterized by a reduced endogen thrombin potential (ETP) (p = 0.031). When the results were analyzed according to the Binet stage, as compared to the controls, the Binet B+C group also presented lower ETP values (p = 0.009). No significant differences were observed between the control and the Binet A groups or between the Binet A and the Binet B + C groups. Although hemostatic alterations may occur in patients with CLL, these parameters do not seem to be useful to indicate disease progression.